2023
DOI: 10.1177/02692155231152567
|View full text |Cite
|
Sign up to set email alerts
|

Effect of robot-assisted gait training on quality of life and depression in neurological impairment: A systematic review and meta-analysis

Abstract: Objective Robot-assisted gait training (RAGT) is often used as a rehabilitation tool for neurological impairments. The purpose of this study is to investigate the effects of rehabilitation with robotic devices on quality of life and depression. Data sources Two electronic databases (MEDLINE and Scopus) were searched for studies from inception up to December 2022. Review methods Randomized controlled trials (RCTs) and non-RCTs were pooled separately for analyses, studying each one’s mental and physical health a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 63 publications
0
6
2
Order By: Relevance
“…In opposite to our findings, the results of a review and meta-analysis by den Brave, M., et al (2023) indicated improvement in depression-related outcomes after RAGT training [68]. Our results are also different from those obtained by Shahin et al (2017), who noted a statistically significant difference between subjects rehabilitated with RAGT and those rehabilitated using conventional methods with DPT.…”
Section: The Impact Of a 7-week Rehabilitation Program On Functionali...contrasting
confidence: 99%
See 1 more Smart Citation
“…In opposite to our findings, the results of a review and meta-analysis by den Brave, M., et al (2023) indicated improvement in depression-related outcomes after RAGT training [68]. Our results are also different from those obtained by Shahin et al (2017), who noted a statistically significant difference between subjects rehabilitated with RAGT and those rehabilitated using conventional methods with DPT.…”
Section: The Impact Of a 7-week Rehabilitation Program On Functionali...contrasting
confidence: 99%
“…Based on the available research, we hypothesized that SCI patients would experience less anxiety and lower levels of depression-related symptoms after both forms of therapy, but that they would do so to a greater extent after RAGT [5,12,13,19,20,41,62,68]. The main objective of our study was to analyze the association of RAGT rehabilitation with symptoms related to depression and anxiety, as well as with clinical status.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the effectiveness of support is only one of the assessed parameters, and problems already occur at the stage of soft tissue modeling or the accuracy of reflecting interactions in relation to reality (e.g., relative movement between the body and the device or force transmission), which is important for personalization [15].Within the Industry 5.0 paradigm, it is also important to examine the impact of exoskeleton rehabilitation and its use in healthy users on quality of life and depression. In general, their positive effect is observed, but these results require further research [16]. The effectiveness of solutions is judged by their impact on body function and structure, not on participation or quality of life [17].…”
Section: Discussionmentioning
confidence: 99%
“…The studies' methodological quality was assessed using the Downs and Black Scale [31] [Appendix B] and the studies were classified as excellent (26)(27), good (20)(21)(22)(23)(24)(25), fair (15)(16)(17)(18)(19), or poor (≤14).…”
Section: Quality Assessmentmentioning
confidence: 99%
“…With recent technological advancements, wearable exoskeletons designed to enhance physical functioning in aging populations [23] are becoming more affordable, lighter, and less constraining [24]. As outlined previously, these devices have demonstrated their potential in patients with neurological conditions, with robot-assisted rehabilitation programs showing positive impacts on gait-related outcomes in stroke and spinal cord injury [18,25,26], but also on quality of life and depressive symptoms in a range of neurological disorders [27].…”
Section: Introductionmentioning
confidence: 99%